2016
DOI: 10.1080/00016489.2016.1214982
|View full text |Cite
|
Sign up to set email alerts
|

The role of long non-coding RNA HOTAIR in the progression and development of laryngeal squamous cell carcinoma interacting with EZH2

Abstract: HOTAIR and EZH2 were over-expressed in LSCC tissue. The higher expression was significantly related to T phase, pathological grades, and risk of lymphatic metastasis of LSCC. Suppressing HOTAIR expression stimulated EZH2 expressing, promoted the proliferation of AMC-HN8 cells, and increased the sensitivity to cis-platinum of the LSCC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…In SCCHN, HOTAIR is able to regulate the activity of the well-known oncogene PTEN, by influencing promoter methylation [ 25 ]. In addition, it plays an important role in the epithelial-mesenchymal transition (EMT) repressing expression of E-cadherin through interaction with EZH2 [ 23 , 27 ]. Overexpression of HOTAIR can also inhibit apoptosis through modification of the mitochondrial membrane and activation of the mitochondrial calcium uptake dependent cell death [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In SCCHN, HOTAIR is able to regulate the activity of the well-known oncogene PTEN, by influencing promoter methylation [ 25 ]. In addition, it plays an important role in the epithelial-mesenchymal transition (EMT) repressing expression of E-cadherin through interaction with EZH2 [ 23 , 27 ]. Overexpression of HOTAIR can also inhibit apoptosis through modification of the mitochondrial membrane and activation of the mitochondrial calcium uptake dependent cell death [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research efforts on the carcinogenesis, development and effective therapeutic methods of HNCs, in which non-coding RNAs (ncRNAs), such as microRNAs (miRNAs) and long ncRNAs (lncRNAs), were inevitably involved, have been conducted [6,7]. Researchers suggested that ncRNAs comprise most of the human transcriptome, while protein-coding genes accounted for only a tiny sliver, less than 2%, of the total genome [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HOTAIR could serve as a biomarker and potential target for therapeutic intervention in LSCC [125]. HOTAIR and the core component of PRC2 EZH2 were overexpressed in LSCC tissues, and reduction of HOTAIR expression stimulated EZH2 expression, promoting proliferation and increasing sensitivity to cis-platinum in LSCC cells [126].…”
Section: Hotair In Head and Neck Cancermentioning
confidence: 99%